Characterization of skin lesions induced by skin‐tropic α‐ and β‐papillomaviruses in a patient with epidermodysplasia verruciformis. (30th November 2014) - Borgogna, C.; Landini, M.M.; Lanfredini, S.; Doorbar, J.; Bouwes Bavinck, J.N.; Quint, K.D.; de Koning, M.N.C.; Genders, R.E.; Gariglio, M.
Summary Epidermodysplasia verruciformis (EV) is a rare, lifelong, autosomal recessive skin disease associated with an unusual susceptibility to infections with ubiquitous β‐human papillomaviruses (β‐HPVs), and in some cases also skin‐tropic α genotypes. In this case report, HPV infection patterns were correlated with pathology and clinical manifestations of skin lesions from a patient with EV, without loss‐of‐function mutations in the EVER genes. HPV infection was investigated by both polymerase chain reaction (PCR) and laser capture microdissection (LCM) PCR, alongside immunofluorescence for the viral proteins E4 and L1. Analysis of eyebrow hair bulbs revealed multiple β‐genus HPV infections, including HPV20 and HPV24, which were consistently found in all 11 skin lesions on the patient. Six lesions were also positive for the skin tropic α‐genotype, HPV27. Clear‐cut differences between two wart‐like lesions, one caused by a skin‐tropic α‐genotype and the other by β‐genotypes (as detected by LCM PCR) are shown, including the high cellular proliferation rate in β‐HPV‐induced lesions. Widespread expression of the early protein E4 was also evident in skin lesions positive for HPV20 by LCM PCR in both tumours and nearby intraepidermal proliferative areas. L1 expression was restricted to areas of intraepidermal proliferation showing productive infection. The patient's inability to control HPV infections is conclusive to the uncontrolled replication of few genotypes from both α and β genera, which cause proliferative lesions with clear‐cut clinical and histological features.